The Belarusian leadership, his country and squalor as depicted in the work of young Belarusian prose writers - McMillin, Arnold (Przegląd Wschodnioeuropejski, 2018)
This article reviews some of the recent texts of young Belarusian prose writers about leadership, the country itself, squalor and alcohol abuse. The attitudes to the Leader in this highly varied selction of stories are at best humorous and more often disrespectful, whilst the picture of Belarus given is of a backward, sometimes squalid country with serious social problems, like violence and excessive drinking.